Hubungan Usia Dan Paritas Dengan Kejadian Preeklamsi Pada Kehamilan - Komalasari, Komalasari; Fauziah, Nur Alfi; Wulandari, Lusia Asih; Suryani, Heni (Universitas Aisyah Pringsewu, 2021)
Preeclampsia is a complication that can occur during pregnancy, where an increase in blood pressure accompanied by proteinuria occurs after the 20th week of pregnancy. Preeclampsia can result in maternal death, prematurity, and it can also cause Intra-Uterine Growth Retardation (IUGR). The data obtained from Abdoel Moloek Hospital in 2018 contained complications of preeclampsia in 327 mothers with 3 babies born dead. The purpose of this research is to identify the connection between age and parity with the incidence of preeclampsia in pregnant women in Dr. H. Abdoel Moeloek Bandar Lampung in 2020.This was quantitative research with cross sectional approach. The subjects were pregnant women treated at the Hospital in 2019, the research was at Dr. H. Abdoel Moeloek Bandar Lampung. The research was conducted in March - April 2020, the population consisted of 513 people and the number of samples was 225 taken by simple random sampling. Data analysis useschi square.The result shows that of 225 respondents, 108 (48.0%) respondents with preeclampsia, 183 (81.3%) respondents with low risk age, 98 (43.6%) respondents with primigravida and grandemultipara parity. There is a connection between age (p-value = 0,000: OR 3,880), and parity with the incidence of preeclampsia at Dr. H. Abdoel Moeloek Bandar Lampung in 2020 (p-value = 0,000: OR 3,848). Suggestions for pregnant women to do a pregnancy checkup at least 4 times during pregnancy in early detection of preeclampsia, the officers should increase the promotion by putting up posters / banners in hospitals about preeclampsia.Preeklamsia merupakan komplikasi yang dapat timbul saat kehamilan, dimana terjadi peningkatan tekanan darah disertai proteinuria yang terjadisetelahumurkehamilan 20 minggu.Preeklamsiadapat mengakibatkan kematianibu, terjadinya prematuritas, serta dapat mengakibatkan Intra Uterin GrowthRetardation (IUGR). Data yang diperolehdariRumahSakitAbdoelMoloektahun 2018 terdapat komplikasipreeklamsi 327 ibudengan 3 bayilahirmeninggal. Tujuanpenelitian diketahui hubunganusiadanparitasdengankejadianpreeklamsipadaibuhamildi RSUD Dr. H. Abdoel Moeloek Bandar Lampung Tahun 2020.Jenis penelitian kuantitatif dengan pendekatan cross sectional. Subjek penelitian adalah ibuhamil yang dirawat di Rumah sakit periode tahun 2019, tempat penelitian di RSUD Dr. H. Abdoel Moeloek Bandar Lampung. Penelitiantelahdilaksanakan pada bulan Maret–April 2020,populasisebanyak 513 orang dan sampel sebanyak 225 yang diambil secara simple random sampling. Analisis data menggunakan chi square.Hasil penelitian diketahui dari 225 responden, sebanyak 108 (48,0%) responden mengalamipreeklamsi, sebanyak 183 (81,3%) respondendenganusiaresiko rendah, sebanyak 98 (43,6%) respondendenganparitasprimigravidadangrandemultipara. Ada hubungan usia(p-value = 0,000 : OR 3,880), dan paritas dengankejadianpreeklamsi di RSUD Dr. H. Abdoel Moeloek Bandar Lampung tahun 2020 dengan (p-value = 0,000 : OR 3,848). Saran bagiibu hamil untuk melakukan pemeriksaan kehamilan minimal 4x selama masa kehamilan dalam mendeteksi dini kejadian preeklamsi.